2016
DOI: 10.1002/pbc.26411
|View full text |Cite
|
Sign up to set email alerts
|

Acute lymphoblastic leukemia in patients with Down syndrome with a previous history of acute myeloid leukemia

Abstract: Patients with Down syndrome (DS) are predisposed to acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) in early and later childhood, respectively, but rarely experience both. We herein discuss four patients with DS with ALL and a history of AML who were treated with various chemotherapies, one of whom later received a bone marrow transplantation. Three patients survived and remain in remission. One patient died of fulminant hepatitis during therapy. No common cytogenetic abnormalities in AML a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…When we reviewed the literature for cases of ALL following AML in patients with Down syndrome, eight cases were reported, published in three manuscripts . A case report by Hellebostad et al from Norway and a case series of four patients by Tomizawa et al in Japan were published with detailed patient demographics and clinical findings (Table ) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…When we reviewed the literature for cases of ALL following AML in patients with Down syndrome, eight cases were reported, published in three manuscripts . A case report by Hellebostad et al from Norway and a case series of four patients by Tomizawa et al in Japan were published with detailed patient demographics and clinical findings (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…When we reviewed the literature for cases of ALL following AML in patients with Down syndrome, eight cases were reported, published in three manuscripts . A case report by Hellebostad et al from Norway and a case series of four patients by Tomizawa et al in Japan were published with detailed patient demographics and clinical findings (Table ) . A clinical trial from the Nordic Society of Paediatric Haematology and Oncology (NOPHO), Dutch Childhood Oncology Group (DCOG), and AML‐BFM study group in 2006 focusing on reduced total dose of etoposide in their Down syndrome cohort by Uffmann et al reported three cases of ALL 1.6‐2.1 years following AML therapy, of which two patients died .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations